2017
DOI: 10.1007/s00405-017-4630-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcanal surgery for vestibular schwannomas: a pictorial review of radiological findings, surgical anatomy and comparison to the traditional translabyrinthine approach

Abstract: 4.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Based on our first experience, TTVN is a feasible and minimally invasive surgical technique. With TTVN, it is possible to perform a neurectomy, avoiding some of the limitations of traditional approaches such as craniotomy, and brain, middle, and posterior fossa manipulations (13,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our first experience, TTVN is a feasible and minimally invasive surgical technique. With TTVN, it is possible to perform a neurectomy, avoiding some of the limitations of traditional approaches such as craniotomy, and brain, middle, and posterior fossa manipulations (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transcanal transpromontorial approaches have been developed to access the inner ear directly through the external auditory canal (EAC) (13). These approaches are an exclusive endoscopic technique providing a direct corridor to the IAC.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment is indicated for progressive tumor growth, progressive hearing loss, control of vertigo, or extension of the tumor into the internal auditory canal. Besides radiation therapy, different surgical techniques are described ranging from transotic tumor resection with middle ear obliteration and blind sac closure of the external auditory canal to transmastoid labyrinthectomy, to microscopic or endoscopic transcanal tumor resection with or without simultaneous CI, to partial/subtotal cochleoectomy with simultaneous CI, or to CI without tumor removal (as in patient 3) [Carlson et al, 2015;Alicandri-Ciufelli et al, 2017;Mazzoni et al, 2017;Xia et al, 2017;Plontke et al, 2018;Ma and Patel, 2020]. The simultaneous resection of the ILS and placement of a CI shows promising results with regard to hearing rehabilitation despite opening of the cochlea [Plontke et al, 2020a].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with the evolution of our own practice, other authors have increasingly demonstrated a role for the endoscope in CPA surgery, either as an adjunct to the microscope, or the primary visualization modality, a trend that may further enhance the utility and dynamism of the retrosigmoid approach across a broad range of clinical contexts. [30][31][32][33] Ultimately, we emphasize the importance of a broad, inclusive, and anatomically oriented skull base education which we anticipate will be well-informed by these dissections and guides that can empower individuals at all stages of training to learn and reproduce the core approach techniques.…”
Section: Clinical Pearls For Selection Of a Retrosigmoid Approachmentioning
confidence: 99%